Accuracy and benefits of 3D bone surface modelling: a comparison of two methods of surface data acquisition reconstructed by laser scanning and computed tomography outputs - Brzobohatá, Hana; Prokop, Josef; Horák, Martin; Jancárek, Alexandr; Velemínská, Jana (Collegium antropologicum, 2012)
The aim of this study is to compare two different methods of frontal bone surface model acquisition. Three dimensional models acquired by laser scanning were compared with models of the same bones acquired by virtual replicas reconstructed from a sequence of computed tomography (CT) images. The influence of volumetric CT data processing (namely thresholding), which immediately preceded the generation of the three-dimensional surface model, was also considered and explored in detail in one sample. Despite identifying certain areas where both models showed deviations across all samples, their conformity can be generally classified as satisfactory, and the differences can be regarded as minimal. The average deviation of registered surface models was 0.27 mm for 90% of the data, and its value was therefore very close to the resolution of the laser scanner used.
Keywords: lasery; zobrazování trojrozměrné; čelní kost; Tomography, X-Ray Computed; antropologie fyzická; počítačová rentgenová tomografie; Anthropology, Physical; lidé; Lasers; Models, Anatomic; Imaging, Three-Dimensional; Humans; anatomické modely; Frontal Bone